The Impact of COVID-19 Pandemic on Local Fiscal Revenue: Empirical Evidence from the Regions with Dominant Tertiary Sectors - Jannah, Aisyah Nurrul; Khoirunurrofik, Khoirunurrofik (Economics and Finance in Indonesia, 2022)
The COVID-19 crisis has devastatingly affected social and economic sectors, including service or tertiary sectors such as banking, insuran;ce, hospitality, telecommunications, and industrial services. The pandemic has also aggravated fiscal conditions along with the slowing economy. This paper aims to assess the impact of COVID-19 on local own-source revenue in regions with dominant tertiary sectors and to examine how a fiscal incentive policy can increase the local own-source revenue. We applied the difference-in-difference panel random effect method by estimating total revenue and local own-source revenue as the outcome variables. The treatment variable is the districts/cities with dominant tertiary sectors of more than 40%, while the control variable is otherwise. The time variables comprise 2018-2019 (before the COVID-19 crisis) and 2020 (at the time of the COVID-19 crisis). The results show that the COVID-19 pandemic causes a decline in total revenue by 2.18%. However, the local own-source revenue increases by 4.62%. In addition, the cross-sectional method was employed to observe the effect of fiscal incentives on local own-source revenue. The results indicate that fiscal incentives, albeit not statistically significant, increase local own-source revenue by 25.7%. It implies that the role of incentives is not yet optimal. The local revenue recovery is mostly due to the large tax base in the tertiary economic regions.